Assessing good operating conditions for intraoperative imaging of melanoma sentinel nodes by a portable gamma camera. Issue 1 (February 2015) - Riccardi, Lucia; Gabusi, Michele; Bignotto, Michele; Gregianin, Michele; Vecchiato, Antonella; Paiusco, Marta
Abstract Objective To provide guidance for reliable identification of low-activity sentinel nodes in the setting of melanoma surgery using a commercial hand-held gamma camera. Methods The average uptake of 99mTc nanocolloid by sentinel nodes was evaluated in 95 excised nodes using a Sentinella 102® (Oncovision, Valencia, Spain) portable gamma camera. The device sensitivity was assessed for different source depths and collimator distances, imaging an 8-mm sphere filled with a known-activity solution of 99mTc. Five nuclear medicine physicians were asked to identify the source at different activity levels and positions within the field of view. For each image the number of signal counts inside a circular region of interest (ROI) was measured, while the variability of ROI counts among operators was assessed. The number of counts providing a minimal, near-constant inter-operator variability was determined as a criterion for a consistent identification of the source. Either the minimum activity or the acquisition time needed to collect the appropriate statistics were then calculated. Results The median SN uptake (0.5%) turned out to be compatible with values reported in the literature. The sensitivity of the compact gamma camera ranged from ∼25 cpm/kBq to ∼1 cpm/kBq. A total of 50 counts in the ROI circumscribing the lymph node-simulating sphere appeared to be a robust criterion for identification of the source. Conclusions Ten megabecquerels of injected activity at the time of surgery and one minute of acquisition allows reliable identification of sentinel nodes for collimator-to-source distances up to 10 cm.